1976
DOI: 10.1107/s0567740876003749
|View full text |Cite
|
Sign up to set email alerts
|

Concerning the β phase of iron(III) oxide

Abstract: fl-Fe203, body centred cubic, la3, a0=9"393 (2) A, Z= 16, D~,= 5"14 g cm -a. In the 24(d) and 8(b) symmetry positions the Fe 3+ ions are octahedrally coordinated, the former being more distorted than the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
2
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 2 publications
2
17
2
1
Order By: Relevance
“…It has an orthorhombic structure and is ferromagnetic with T C = 480 K 6,10 . β-phase is another new phase having a bixbyite structure and exhibits antiferromagnetic feature with a Neel temperature (T N ) of 119 K [11][12][13] . α-Fe 2 O 3 is the thermodynamically most stable among these four polymorphs.…”
mentioning
confidence: 99%
“…It has an orthorhombic structure and is ferromagnetic with T C = 480 K 6,10 . β-phase is another new phase having a bixbyite structure and exhibits antiferromagnetic feature with a Neel temperature (T N ) of 119 K [11][12][13] . α-Fe 2 O 3 is the thermodynamically most stable among these four polymorphs.…”
mentioning
confidence: 99%
“…1. There is the formation of the cubic phase of Fe 2 O 3 [12] after 200°C that still remains in a small concentration at 400°C, noticed by the peak near 38°. The vertical bars denote the cubic phase as predicted by cubic symmetry.…”
Section: Resultsmentioning
confidence: 90%
“…The Zboril et al (1999) study is closely related to the present study in that they prepared b-Fe 2 O 3 by heating Fe 2 (SO 4 ) 3 above 500°C. The phase b-Fe 2 O 3 is cubic, Ia3, with a = 9.404 Å (Ben-Dor et al 1976). In the present study, the a cell parameter was found to decrease with increasing temperature, from 9.465(1) Å at 600°C to 9.447(1) Å at 680°C.…”
Section: From 400 To 500°cmentioning
confidence: 99%